Project in Entrepreneurship Tintaya Spirit - Cortés Orrillo, César Eduardo (2018)
The present project evaluates the potential of the business idea; the possibility of creating an Eco-hotel on Lobitos Beach, located in the northern coast of Peru; more precisely in the province of Talara, near to Piura city; ideal place with sandy beaches to practice water sports, mainly surfing. And where, despite the presence of some hotels, there is none that stands out for a differentiation in their accommodation and services. Also analyzes its relationship with current industry, the needs of the target market, the ability of entrepreneurs to establish and manage the business, as well as the financial needs of the project. The development of the business idea we want to combine the passion for share our best with people, nature, culture and activities related to the sea, with our knowledge and experience in the field of business administration. Our goal goes beyond creating a profitable and lasting business over time, we also want to highlight the Peruvian culture related to the region, generate a positive impact on all the stakeholders, especially on the environment and the inhabitants of the area.